Agriculture of the Republic of Turkey (1923-1941) in the Light of Yugoslav Sources - Virijević, Vladan A. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Signing the Agreement on the Establishment of Friendly Diplomatic Relations between the Republic of Turkey and the Kingdom of Serbs, Croats, and Slovenes (the Kingdom of Yugoslavia since 1929) on November 28, 1925, provided bases for mutual economic connecting. Concerning the fact that economies of both countries had dominantly agrarian character, they were often rivals to one another in the world markets. Because of that, Yugoslav government aimed at gathering data on the development and modernization of Turkish agriculture by means of its diplomatic representative bodies. In this paper, on the basis of unpublished archival sources, newspapers articles and relevant literature, the following issues will be presented: the stateand characteristics of the Turkish agrarian issues during Ataturks’s era: the capacity of agricultural production (agriculture, cattle breeding), measures and efforts for its improvement (introducing new kinds  and breeds, land-improvement and irrigation projects, the use of modern agro-technical measures, preventing cattle infectious diseases, agrarian reforms, etc.), and the export of agrarian products.
Keywords: agriculture; Republic of Turkey; the Kingdom of Serbs, Croats and Slovenes (Yugoslavia); Ataturk’s era; agrarian reform